Methylation status of HPV16 E2-binding sites classifies subtypes of HPV-associated oropharyngeal cancers - Reuschenbach, Miriam; Prigge, Elena-Sophie; Lorenzo Bermejo, Justo; Kalteis, Martin Simon; Vinokurova, Svetlana; Knebel Doeberitz, Magnus von (Cancer, 2015)
BACKGROUND The human papillomavirus (HPV) E2 protein is a transcriptional repressor of the oncogenes E6/E7 and loss of E2 function is considered a key step in carcinogenesis. Integration of HPV into the host genome may disrupt the E2 gene. Furthermore, methylation of CpG dinucleotides in E2-binding sites (E2BSs) in the HPV upstream regulatory region may interfere with transcriptional repression of E6 and E7 by E2. The authors hypothesized that the CpG methylation status of E2BS identifies subtypes of HPV type 16 (HPV16)-associated oropharyngeal squamous cell cancers (OPSCC) in association with E2 gene integrity and viral integration. METHODS Methylation of 10 CpG dinucleotides within the upstream regulatory region, encompassing E2BSs 1, 2, 3, and 4, was quantitatively analyzed by bisulfite pyrosequencing in 57 HPV16-associated OPSCC cases. E2 status was analyzed by gene amplification and quantitative real-time reverse transcriptase-polymerase chain reaction. Viral integration was determined by integration-specific polymerase chain reaction methods. RESULTS Three subgroups with differential methylation at E2BS3 and E2BS 4 were identified: 1) complete methylation (>80%) associated with the presence of integrated HPV genomes with an intact E2 gene; 2) intermediate methylation levels (20%-80%) with predominantly episomal HPV genomes with intact E2; and 3) no methylation (<20%) with a disrupted E2 gene. Patients with high methylation levels tended to have a worse 5-year overall survival compared with patients with intermediate methylation (hazard ratio, 3.23; 95% confidence interval, 1.13-9.24 [P = .06]). CONCLUSIONS Methylation of E2BS3 and E2BS4 in OPSCC is associated with E2 integrity and viral physical status. It might explain deregulated viral oncogene expression in the presence of E2. The prognostic significance of E2BS methylation for patients with HPV-associated OPSCC needs to be analyzed further
Gesehen am 11.04.2017